Germany's vocational education and training system in transformation : changes in the participation of low- and high-achieving youth over time - Jacob, Marita [Verfasser]; Solga, Heike [Verfasser] (My University, 2015)
"The aim of this article is to systematize empirical findings from the German Life History Studies, which allow a (long-term) historical perspective on changes in Germany's vocational education and training (VET) system. We consider two aspects. First, we examine access to and patterns of VET participation. Second, we discuss the impact of changes in individual educational behavior on skill formation institutions. In doing so, we contribute new insights concerning the interplay between individuals and the German VET system. Life courses not only are structured by institutions but also may 'trigger' institutional changes. We assume that the two 'trigger' groups at the boundaries of the VET system - that is, low-achieving and high-achieving youth - pose the greatest challenge to its institutional structure and are therefore useful groups to examine to learn more about the performance of the German VET system and the relation between individual educational behavior and institutional change." (Authors' abstract, BIBB-Doku)
Keywords: T 4.5 Soziologie; P 1.1 Jugendliche; G 1.3.2 Bildungsverhalten und -verläufe; I 2.1 Deutschland; Berufsbildungssystem; Lebensverlaufsforschung; Jugendlicher; Geringqualifizierter; Hochqualifizierter; Bildungsabschluss; Bildungsbeteiligung; Bildungsverhalten; Bildungsverlauf; Bundesrepublik Deutschland